Evaluation of Temporal and Spatial Changes in Ecological Environmental Quality on Jianghan Plain From 1990 to 2021 - Ren, Wei; Zhang, Xuesong; Peng, Hongjie (Frontiers in Environmental Science, 2022)
Located in the middle reaches of the Yangtze River, Jianghan Plain is an important part of the middle and lower reaches of the Yangtze River Plain, and together with Dongting Lake Plain, it is known as the Two-Lake Plain. It is a well-developed agricultural area and is an important source of grain in China, as well as one of the major cotton-producing areas, and aquaculture is also an important local industry. With the rapid development of urbanization in China, the impact of human activities on the ecological environment of Jianghan Plain has become increasingly obvious in recent years, and how to timely and objectively assess spatial and temporal changes in ecological environmental quality is of great practical significance for the sustainable development of the region and the construction of an ecological civilization. The Google Earth Engine platform was used to optimize the reconstruction of Landsat TM/OLI images of Jianghan Plain from 1990 to 2021, coupled with four indicators of the natural ecological environment such as the Normalized Difference Vegetation Index, WET, Normalized Difference Soil Index, and Land Surface Temperature to construct the remote sensing ecological index (RSEI) and evaluate the spatial and temporal changes in ecological environmental quality on Jianghan Plain. The results showed that the mean RSEI values in 1990, 1998, 2006, 2014, and 2021 were 0.667, 0.636, 0.599, 0.621, and 0.648, respectively, indicating that the overall ecological environmental quality of Jianghan Plain showed a decreasing trend from 1990 to 2006 and an increasing trend from 2006 to 2021. Degradation was most serious from 1990 to 1998, accounting for 44.86% of the total area, and improvement was most obvious from 2006 to 2014, accounting for 26.64% of the total area. Moran’s I values from 1990 to 2021 were 0.531, 0.529, 0.525, 0.540, and 0.545, respectively, indicating that the spatial distribution of ecological environmental quality was positively correlated. The local spatial clustering of the RSEI local indicators of spatial association showed that H-H clustering areas on Jianghan Plain were mainly distributed in the northern and western regions, and L-L clustering areas were mainly distributed in the densely populated eastern regions with frequent human activities. The results can provide a theoretical basis for ecological environmental protection and improvement on Jianghan Plain.